2012
DOI: 10.1177/1934578x1200700624
|View full text |Cite
|
Sign up to set email alerts
|

cis-Aconitic Anhydride Ethyl Ester and Phenolic Compounds from the Seeds of Alisma orientale

Abstract: From the seeds of Alisma orientale, cis-aconitic anhydride ethyl ester and cis-2,4,5-trihydroxycinnamic acid were isolated, together with nine known phenolic compounds and a megastigmane sesquiterpene. All compounds are reported for the first time from Alisma species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Chromatograms of ARAE detected main compounds with four peaks: compound 1 ( m / z 281.1641 [M+H] + ), compound 2 ( m / z 295.1812 [M+H] + ), compound 3 ( m / z 265.1696 [M+H] + ) and compound 4 ( m / z 279.1854 [M+H] + ). These compound 1 ((R)-1-(1-phenyl-3,4-dihydropyrrolo[1,2-a]pyrazin-2(1H)-yl)pent-4-en-1-one (101c); C 18 H 21 N 2 O), compound 2 (trans-N-Benzyl-1-methyl-4-phenylpyrrolidine-3-carboxamide; C 19 H 23 N 2 O), compound 3 (N-{(E,2E)-2-[(2,6-Dimethylphenyl)imino]ethyliden}-2,6-dimethylaniline; C 18 H 21 N 2 ) and compound 4 ((E)-N-(2-phenyl-1-(piperidin-1-yl)ethylidene)aniline; C 19 H 23 N 2 ) were identified as phenolic compounds based on MS data and reference (12,21–24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatograms of ARAE detected main compounds with four peaks: compound 1 ( m / z 281.1641 [M+H] + ), compound 2 ( m / z 295.1812 [M+H] + ), compound 3 ( m / z 265.1696 [M+H] + ) and compound 4 ( m / z 279.1854 [M+H] + ). These compound 1 ((R)-1-(1-phenyl-3,4-dihydropyrrolo[1,2-a]pyrazin-2(1H)-yl)pent-4-en-1-one (101c); C 18 H 21 N 2 O), compound 2 (trans-N-Benzyl-1-methyl-4-phenylpyrrolidine-3-carboxamide; C 19 H 23 N 2 O), compound 3 (N-{(E,2E)-2-[(2,6-Dimethylphenyl)imino]ethyliden}-2,6-dimethylaniline; C 18 H 21 N 2 ) and compound 4 ((E)-N-(2-phenyl-1-(piperidin-1-yl)ethylidene)aniline; C 19 H 23 N 2 ) were identified as phenolic compounds based on MS data and reference (12,21–24).…”
Section: Discussionmentioning
confidence: 99%
“…AR compounds that have been discovered include terpenoids (11), phenolic (12), polysaccharides (13), carbohydrates, proteins, amino acids, etc (5). Diuretic activity investigations have shown that the alisol A content in AR has a similar diuretic effect with hydrochlorothiazide, and alisol A 24-acetate and hydrochlorothiazide increased the excretion of Na + and K + in rats (14).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, only five phenylpropionic acids were obtained from A. orientale and A. plantago‐aquatica through preparative HPLC eluted with MeOH‐H 2 O as mobile phase (Figure 6), namely N‐trans‐ feruloyl‐ N′‐cis ‐feruloyl‐cadaverine ( 110 ), N,N′‐trans ‐diferuloyl‐3‐oxo‐cadaverine ( 111 ), N‐trans‐ feruloyl‐ N′ ‐ cis ‐feruloyl‐3‐hydroxy‐ cadaverine ( 112 ), N,N′‐cis‐ diferuloyl‐3‐hydroxy‐cadaverine ( 113 ), N‐trans‐p‐ coumaroyl‐ N′ ‐ trans ‐feruloyl‐3‐hydroxy‐cadaverine ( 114 ), and plantain A ( 115 ) (Xin et al, 2017). In addition, cis ‐2,4,5‐trihydroxycinnamic acid ( 116 ) and cis ‐aconitic anhydride ethyl ester ( 117 ) were also isolated from the seeds of A. orientale by Zhao et al (2012).…”
Section: Phytochemical Constituents Of the Genus Alismamentioning
confidence: 99%